2020
DOI: 10.1002/srin.202000055
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics Model of the Hearth Lining State

Abstract: The blast furnace (BF) is a huge counter-flow reactor to produce pig iron. The molten pig iron and by-product slag are accumulated at the hearth of the furnace, from where they are regularly tapped. The campaign life of the BF is governed by the wear of the hearth refractory. Once the residual thickness of the hearth lining is critically low, it must be repaired during a long-term stoppage, which is quite costly. Therefore, it is essential to keep track of the residual lining thickness not only for the better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Still, it should be kept in mind that the accuracy of erosion models depends on the validity of the modeling assumptions. In particular, brittle lining layers of low conductivity may lead to inaccurate estimates of the progress of the erosion profile, and the occurrence of such should be detected by other means [56,57]. erosion experienced during the campaign.…”
Section: Hearth Wear Profilementioning
confidence: 99%
“…Still, it should be kept in mind that the accuracy of erosion models depends on the validity of the modeling assumptions. In particular, brittle lining layers of low conductivity may lead to inaccurate estimates of the progress of the erosion profile, and the occurrence of such should be detected by other means [56,57]. erosion experienced during the campaign.…”
Section: Hearth Wear Profilementioning
confidence: 99%
“…The model demonstrated that viscous fingering may occur as the liquid-gas interface was near the outlet during the simulation. Kaymak et al [23] developed a simplified 3D CFD model to simulate the tilting of both slaggas and slag-iron interfaces during the hearth tapping process. To reduce the computational load, instead of the common used multiphase flow model, a single slag phase flow in coke packed bed with two moving interfaces has been formulated and implemented in this model where the interface movements were modelled by the moving mesh physics.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, to help explain refractory temperature measurements and locate the 1150°C isotherm, numerical modelling has been applied and can be classified into two categories: (1) refractory conduction modelling, for one-, two-or three-dimensional (1D, 2D or 3D) conditions within the hearth refractory [3][4][5][6][7][8]; (2) modelling based on coupled fluid flow, heat and mass transfer in a domain including hearth refractory and the molten liquid bath [4,[9][10][11][12][13][14][15][16][17][18][19][20]. The former is mainly based on the inverse heat conduction technique considering heat transfer in the refractory and skull (solidification layer) while the latter provides more information about molten iron (and slag) flow and the heat transfer within the hearth.…”
Section: Introductionmentioning
confidence: 99%